Improved Skin Penetration of Hydrophobic Glycyrrhetinic Acid Smart- Crystal® Compared to Its Water Soluble Salt - Mishra, Moumita; Shegokar, Ranjita; Gohla, Sven; Muller, Rainer H. (Drug Delivery Letters, 2017)
Aim and Objective: Aim of this study was to evaluate the skin penetration performance of water insoluble glycyrrhetinic acid (GHA) nanocrystals in comparison to the gel and o/w nanoemulsion formulation of water soluble glycyrrhizic acid salt (GA). Methods: The GHA-SmartCrystal® was prepared using bead milling followed by high pressure homogenization. The nanocrystals and o/w nanoemulsion were prepared by homogenization. All formulations were tested for their in vitro penetration and in vivo permeation performance. Results and Discussion: The SmartCrystal® and o/w nanoemulsion had mean particle size of 158 nm and 183 nm, respectively. The zeta potential values of both the formulations were about -30 mV which indicated a good physical stability. After 24 h, the cumulative in vitro skin penetration was 3.29 μg/cm2, 7.13 μg/cm2, 4.24 μg/cm2 and 3.64 μg/cm2 or GHA-coarse suspension, GHA SmartCrystal®, o/w nanoemulsion and GA-gel, respectively in pig ear skin. The cumulative amount of active recovered from the tapes was 4.52 μg/cm2, 93.24 μg/cm2, 9.64 μg/cm2 and 5.55 μg/cm2 for GHA coarse suspension, SmartCrystal®, GA-o/w nanoemulsion and GA-gel, respectively suggesting superior performance of developed nanocrystals. Conclusion: SmartCrystals and nanocrystals showed higher cumulative drug penetration when tested in vitro and in vivo. SmartCrytals offered superior performance of GHA due to smaller particle size and enhanced penetration property. SmartCrytals can be easily mixed with any topical or dermal dosage carriers like gel, cream or lotion for ease of application.
Keywords: glycyrrhizic acid (GA)